Impact of basalt fiber reinforced concrete in protected buildings: a review - Vatin, Nikolai Ivanovich; Hematibahar, Mohammad; Gebre, Tesfaldet Hadgembes (Frontiers in Built Environment, 2024)
This study investigates on the impact of basalt fiber reinforcement concrete in protected building and structures. Basalt fibers, derived from the melting of basalt rock at temperatures ranging from 1500 to 1700 degrees Celsius, are recognized as sustainable and environmentally friendly fiber materials. Various studies have revealed differing optimal percentages of basalt fibers for enhancing the mechanical and chemical properties of concrete. The objectives of this paper are to investigate the effects of basalt fibre reinforcement on mechanical properties like tensile, compressive, and bending strengths. Additionally, performance indicators like void content, water absorption, chloride ion permeability, alkali and slag resistance, temperature stability, shrinkage characteristics, and abrasion resistance will be evaluated. Basalt fibre is typically utilised to increase the mechanical properties and durability of concrete, which has an impact in the effect on protected buildings and structures. The findings indicate that the most effective percentage range for improving mechanical properties lies between 0.1% and 0.3% of basalt fibers. Notably, concrete reinforced with basalt fibers demonstrates superior mechanical and chemical performance in alkaline environments compared to other fiber types. Moreover, the addition of 0.5% basalt fibers to concrete has been shown to significantly reduce chloride ion penetration, as evidenced by a decrease in RCPT load from 2500 (C) to 1900 (C), indicative of enhanced chloride resistance. Reinforced concrete containing basalt fibers exhibits remarkable temperature resistance, withstanding temperatures exceeding 800 degrees Celsius due to its high-water absorption capacity. Additionally, basalt fibers exhibit resilience at temperatures up to 200 degrees Celsius. However, it is noted that the introduction of 0.14% basalt fibers leads to a slight increase in water absorption from 4.08 to 4.28. In general, basalt fibres are beneficial to many aspects of concrete; they strengthen resistance to temperature, alkali, acid exposure, and chloride while also improving mechanical qualities such as bending and tensile strength. The development of basalt fibres that extend building lifespans and improve concrete quality for structural engineering applications is making encouraging strides, according to all the results.